ROLE OF NANO AND METALLIC BORON FOLIAR NUTRITION ON WATER STRESS REDUCING IN SWEET CORN YIELD AND ITS COMPONENTS - M. T. Riwad,; M. K. Alag, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A field experiment was conducted in the experimental field of the Crop Sciences Department at the College of Agricultural Engineering Sciences - University of Baghdad during fall seasons of 2021 and 2022. The aim of this study was to investigate the role of nano and metallic boron foliar nutrition on yield, components, water use efficiency, and water consumption under water stress for sweet corn (Zea mays L.). Randomized Complete Block Design was used within split -plot arrangement with three replicates, where the main plots included three levels of water stress (irrigation at 40, 60, and 80% of available water) coded as W1, W2, and W3, respectively. The nano and metallic boron spray concentrations represented 5, 10, 20, and 40 mg L-1 coded as N1, N2, M1, and M2, respectively. Results showed that nano and metallic boron concentrations significantly affected all the studied traits. The concentration of 5 mg L-1 of nano boron N1 significantly exceeded other concentrations under study in increasing ear length, number of rows per ear, number of grains per row, and weight of 500 grains, which positively reflected on improving grain yield of 5.93 and 5.96 t ha-1. The interaction between water stress treatments and nano and metallic boron concentrations was significant for all the studied traits except for ear length.